QTL detection and candidate gene study for traits related to food quality and safety in sheep (meat and dairy) production within the framework of a European research contract called 'genesheepsafety' - Barillet F.; Bodin L.; Chemineau P.; Chilliard Y.; Cribiu E.; Elsen J.M.; Gruner L. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
The 'genesheepsafety' project addresses the safety and quality of food in the sheep production chain using genetics. It concerns research partners from France, UK, Italy and Spain involved in a European contract (QLK5-2000-00656) of the 5th Framework Programme. The project (February 2001 - July 2004) will share genetic resource populations and the genotyping of the animals using microsatellite markers. The traits measured, related to food quality and safety, include CLA (conjugated linoleic acid) of milk, mastitis resistance and milkability, nematode parasite resistance, nasal botfly resistance and out of season breeding. It is planned to study both candidate genes or functional genomics for those traits, and QTL analysis. Outputs include knowledge on food and quality traits, QTL and candidate genes, in order to implement breeding strategies on those traits.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)